Penguasaan bahasa wanita pekak dan impak kepada pemerolehan bahasa anak - Abd Nasir, Siti Noridayu; Abdul Halim, Hazlina; Yahaya, Ahmad Shuib (University Malaysia Perlis, 2022)
The impact on a child’s language acquisition starts from the initial environment from birth onwards. Expression by parents influences a child’s language acquisition. However, the language 42 acquisition process of children who have mothers with physical disabilities (OKU) hearing impaired problems is different. This is because, the deaf problem experienced affects the language proficiency. Therefore, this study has three research objectives. First, it was conducted to identify the factors and impacts that occur in the acquisition of mother tongue with hearing impairment. Jean Piaget’s theory was applied in the data analysis process of this study involving mother tongue mastery and child language acquisition. Second, to examine the level of language acquisition of children under the care of deaf women. Finally, the third aims to look at the correlation between Jean Piaget's Theory with the language proficiency of mother and child respondents. This study is a qualitative study that goes through in-depth study of the respondents. In conclusion, through the findings of the study showed that the mastery of mothers with hearing problems affects the language acquisition of children in care. In fact, family background factors role plays to that is a factor of acquired language proficiency. However, language acquisition that is often repeated and used regularly has a good effect to improve language acquisition in an aspect.